Stroke Risk Stratification in Incident Atrial Fibrillation: A Sex-Specific Evaluation of CHA2DS2-VA and CHA2DS2-VASc - Jose L. Clua-Espuny; Anna Panisello-Tafalla; Jorgina Lucas-Noll; Eulàlia Muria-Subirats; Teresa Forcadell-Arenas; Juan M. Carrera-Ortiz; Pedro Molto-Balado; Josep Clua-Queralt; Immaculada Fusté-Anguera; Silvia Reverte-Vilarroya (Journal of Cardiovascular Development and Disease, 2025)
(1) Background: In the absence of locally validated tools, the CHA2DS2-VA score has been suggested as a substitute for the CHA2DS2-VASc score. This study compared the potential discrepancies between these scores. (2) Methods: The observational, retrospective, and community-based study included a cohort of 3370 patients with a new diagnosis of atrial fibrillation (AF) between 1 January 2015 and 31 December 2024. (3) Results: AF prevalence was 8.4%, which was significantly higher in men. The mean age was 80.1 (SD ± 6.24) years. Women (42.8%) were older (80.9 SD ± 6.1 vs. 79.5 SD ± 6.23; p < 0.001). Men had more instances of diabetes mellitus, peripheral vascular disease, coronary artery disease, and chronic obstructive pulmonary disease, as well as a higher Charlson Comorbidity Index. Conversely, women exhibited a higher proportion ≥75 years, including cognitive impairment, dyslipidemia, and higher stroke risk, as assessed by the CHA2DS2-VASc score (p < 0.001) but not by the CHA2DS2-VA score (p = 0.071). The CHA2DS2-VA score reduced the sex-based risk stratification differences, and only 3.2% of women were reclassified as being at very low risk (CHA2DS2-VA < 2). (4) Conclusions: The CHA2DS2-VA score notably redefined sex-based thromboembolic risk stratification profiles, with no sex-based disparities in the selection of OAC treatment modality. The clinical utility of CHA2DS2-VA remains a subject of ongoing debate.